Post partum blues; Sebuah tinjauan literatur - Yunitasari, Eva; Suryani, Suryani (Wellness And Healthy Magazine, 2020)
Postpartum blues are strongly influenced by internal and external factors. Where the results of the assessment of patients said they felt confused, fatigue, lack of sleep, irritability and anxiety because their milk had not come out since 5 days postpartum. The patient also said that he did not get enough attention and help from her husband because her husband often went out of town. This type of research is research using the literature study method or literature review. The subject of this research was about postpartum mothers. The results of this study factors are factors that affect the postpartum blues are psychological factors that include family support khusu 's her husband. Demographic factors include age and parity, physical factors caused by physical fatigue due to the activities of babysitting, breastfeeding, bathing, changing diapers, and social factors include socioeconomic, education level, marital status. Factors that influence postpartum blues are psychological factors that include family support, especially the husband. It is expected to be able to detect early the occurrence of postpartum blues events so that actions can be taken in accordance with the conditions and needs of the mother. It is hoped that the results of this study will be additional information regarding postpartum blues